Forming a formula from a-b=c-d

  1. Hi, I am beginner in mathematics , I have the following relationship:

    a-b=c-d

    I need to calculate c under the assumption that a, b and d are known values.
    I got c=a-b+d
    and c=a/b*d

    can I use any other formulas?!!
     
  2. jcsd
  3. phinds

    phinds 9,372
    Gold Member

    c=a-b+d follows directly from the stated relationship. Where did you get c=a/b*d ???
     
  4. Mark44

    Staff: Mentor

    What you got above is correct. To solve for c, add d to both sides of the equation.

    I don't know how you got the equation below, but it's incorrect.
    The equation you started with is very simple, so the only possible differences are how the three terms on the other side are arranged, with a total of six ways.

    c = a - b + d
    c = a + d - b
    c = d + a - b
    c = d - b + a
    c = -b + a + d
    c = -b + d + a
     
  5. c=a-b+d follows from a-b=c-d

    c=a/b*d follows from a/b=c/d

    Did you write it down in a way that your -'s look like /'s ?
     
Know someone interested in this topic? Share this thead via email, Google+, Twitter, or Facebook

Have something to add?

0
Draft saved Draft deleted